2017
DOI: 10.1002/fsn3.553
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and structural properties of enzyme‐induced gelation of milk proteins by ficin and Polyporus badius

Abstract: The rheological and microstructural characteristics of ewes’ milk curd obtained by coagulating with milk‐clotting enzymes, including ficin extract and Polyporus badius were evaluated. The gelation of milk was examined by small amplitude oscillatory shear measurements (SAOS). Different concentrations of ficin and P. badius extracts (1, 3, and 5%) were utilized to coagulate milk proteins. The ewes’ samples containing ficin and mushroom enzymes were heated from 25 to 45°C at a heating rate 1°C/min and kept for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In another research, ficin was compared to Polyporus badius extract in the coagulation of milk by analyzing the rheological and microstructural characteristics of ewes milk curd [117]. The gels produced by P. badius gels were more viscous and with a softer texture than the ficin gels.…”
Section: 3-milk Clottingmentioning
confidence: 99%
See 1 more Smart Citation
“…In another research, ficin was compared to Polyporus badius extract in the coagulation of milk by analyzing the rheological and microstructural characteristics of ewes milk curd [117]. The gels produced by P. badius gels were more viscous and with a softer texture than the ficin gels.…”
Section: 3-milk Clottingmentioning
confidence: 99%
“…The gels produced by P. badius gels were more viscous and with a softer texture than the ficin gels. That is, they have higher moisture and lower protein contents presenting a more compact structure [117]. In another example, the coagulation of ewe milk was produced using extracts from Cynara scolymus L. cv.…”
Section: 3-milk Clottingmentioning
confidence: 99%
“…The evolution of the complex modulus (G) with time is shown in Figure 4 , and a sigmoidal increase in G with time was observed. Shabani et al ( 2018 ) reported that G′ value was higher than that of G′′ at the outset and throughout the experiment for ficin and Polyporus badius extract, revealed the association of proteins. Bohlin et al ( 1984 ) pointed out that this is the typical behavior of the secondary phase of milk coagulation.…”
Section: Resultsmentioning
confidence: 94%
“…The absence of fat may be responsible for this observation. Shabani et al ( 2018 ) reported that the concentration of enzymes was profoundly affected the gelation of milk protein. In addition, the milk proteins need more time to aggregate at lower concentrations of mushroom enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation